Structural and dynamics behavior of native endoglucanase from fusarium oxysporum - Ibrahim Ali , Noorbatcha; Waesoho, S.; Hamzah, Mohd. Salleh (INSI Publications, 2012)
Molecular dynamics methods are very useful tool in understanding the behavior of the enzymes at higher temperatures. In this work we employ molecular dynamics simulation of an endoglucanase from Fusarium oxysporum to examine its structural and dynamics behavior at 80°C, by analyzing the root mean square derivation (RMSD) from the initial structure. The RMSD values of coil and turn regions are found to be higher compared to helix and β-sheet regions. The surface area of the structure is found to have larger RMSD compared to the buried part of the enzyme, due the β-jelly roll nature of the enzyme. For the same reasons, the number of hydrogen bonds between among residues in β-sheet is found to larger compared to those in the coil regions. However, the number of hydrogen bonds between water and proteins is highest in turn regions and lowest in helix regions. The turn regions connecting the 310-helix are found to fluctuate more rapidly compared to the other parts of the enzyme. These factors can explain the loss of the activity of the enzyme at high temperatures.